2003
DOI: 10.1097/01.blo.0000092983.12414.e9
|View full text |Cite
|
Sign up to set email alerts
|

Ranawat Award Paper: Predicting Total Knee Replacement Pain

Abstract: To describe the natural history of pain after total knee arthroplasty and to identify factors predicting excessive postoperative pain, we used a prospective, observational study assessing clinical and radiographic variables preoperatively and at 1, 3, 6, and 12 months after knee replacement. Data sources included the visual analog pain scale and other measures of patient health, psychologic state, and component reliability. Regression analyses were conducted to identify specific factors predictive of postopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
206
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 524 publications
(217 citation statements)
references
References 15 publications
8
206
3
Order By: Relevance
“…Six cohorts reported outcomes in hip replacement, 49,51,58,102-104 and 11 in knee replacement patients. 47,49,50,58,102,[105][106][107][108][109][110] The main reasons for exclusion at this stage were lack of a pain outcome separate from an overall outcome score or the presentation of results as means only. Patient and study characteristics are summarised briefly in Table 1 and in more detail with outcome data in Appendix 4.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Six cohorts reported outcomes in hip replacement, 49,51,58,102-104 and 11 in knee replacement patients. 47,49,50,58,102,[105][106][107][108][109][110] The main reasons for exclusion at this stage were lack of a pain outcome separate from an overall outcome score or the presentation of results as means only. Patient and study characteristics are summarised briefly in Table 1 and in more detail with outcome data in Appendix 4.…”
Section: Resultsmentioning
confidence: 99%
“…105 Two studies were in patients from multiple centres, 58,102 six studies were in patients treated at a single centre 47,[106][107][108][109][110] and one study reported all patients operated on by one surgeon. 50 Cohorts were generally similar with regard to patient age (range of means or medians 66-76 years) and sex (range of percentage female 54-86%), and the indication was osteoarthritis in ≥ 94% of patients when specified. Losses to follow-up ranged from 0% to 43.5%.…”
Section: Total Knee Replacementmentioning
confidence: 91%
See 3 more Smart Citations